Different forms of consumers' impulsive buying behavior - Alimpić Stefan; Nenad Perić (Anali Ekonomskog fakulteta u Subotici, 2020)
In this manuscript, authors first define and explain the concept, as well as the types of impulsive (unplanned) purchases, and then the techniques that can be used to encourage consumers to perform them. In addition, the types of people who have the impulsive buying tendency are defined. Finally, authors define and analyze factors in connection with consumers' behavior which can be viewed as triggers for impulsive purchase of a product and/or services. A review of the literature presented in this paper can help sales managers and companies to better understand the causes of consumers' impulsive behavior. In addition, the information presented can be used by brand managers when compiling business plans.